The role of Ge2Sb2Te5 in enhancing the performance of functional plasmonic devices. (March 2020) - Gerislioglu, B.; Bakan, G.; Ahuja, R.; Adam, J.; Mishra, Y.K.; Ahmadivand, A.
Abstract: Phase-change materials (PCMs) and compounds enable a combination of features for implementing advanced and multifunctional nanophotonic applications. Possessing opposite phases at different temperatures and toggling between amorphous to crystalline states (set-reset states) lead to dramatic changes in the optical characteristics of them. In this review, we focus on the recent progresses in the field of multifunctional nanoplasmonics based on integrated PCMs. More precisely, we explain the use of a well-known phase-change compound, Ge2 Sb2 Te5 (GST), in tailoring efficient and tunable plasmonic devices. Formed by the chalcogenide family and as a notable member of PCM components, GST has received a growing attention in the past years for developing non-volatile random access memory technology and optical systems. The reconfigurable and non-volatile characteristics of GST allow for the manipulation of light in subwavelength geometries. Based on the knowledge in the field of functional nanophotonic devices, we demonstrate promising paths that have been introduced to improve the efficiency of optical devices based on the PCM technology. Furthermore, we discuss the unique properties of GST in designing of modern plasmonic and nanophotonic tools. Finally, we present an outlook for the future opportunities of GST-mediated nanoplatforms, including all-optical instruments, beam-steering metasurfaces, and nanoscale switches and absorbers. Graphical abstract: Image 1 Highlights: Ge2 Sb2 Te5 is a promising member of phase-change compounds with a broad range of applications in functional nanophotonics. Formed by chalcogenide family, Ge2 Sb2 Te5 has been employed for developing non-volatile random access memory technology. The reconfigurable and non-volatile functionality of Ge2 Sb2 Te5 allows for manipulation of light in deep-subwavelength geometries. Ge2 Sb2 Te5 -mediated plasmonic metaplatforms have strong potential to be employed used in implementing advanced technologies.